Minat dan Penggunaan Fintech PayLater Pekerja Urban Pelanggan Traveloka dan GoJek Sebelum dan Selama Pandemi Covid 19 di DKI Jakarta - Adirinekso, Gidion P. (Journal of Management and Business Review, 2021)
The Covid 19 pandemic hit Indonesia, and one of the impacts on payment system activities. The PayLater application system develops as a method of bailout payment from companies. Two large companies, Traveloka and GoJek, offer a later payment system associated with their application. However, OVO provided the same thing for companies that work with them. When a pandemic occurs, will it change the interest and use of the PayLater application? This study looks for factors that influence the part and use of PayLater for urban workers in DKI Jakarta. Based on the second generation of Unified Theory Acceptance and Use of Technology (UTAUT2) as a theoretical basis for finding these factors using PLS-SEM. The multi-group analysis shows any differences in terms of transactions, gender, type of generation during the pandemic. There were 1201 urban workers surveyed in DKI Province. The research contribution is in multi-group analysis and has practical implications for Traveloka, GoJek, and OVO companies. Another study should consider cost switching for urban workers when new fintech emerges in terms of costs, benefits, and tenor times. We can use panel data, where the same respondents are observed in the period before, during, and after the period.